Unusually weak irradiation effects in anisotropic iron-based superconductor RbCa2Fe4As4F2 - Daniele Torsello; Daniele Torsello; Erik Piatti; Michela Fracasso; Michela Fracasso; Roberto Gerbaldo; Roberto Gerbaldo; Laura Gozzelino; Laura Gozzelino; Xiaolei Yi; Xiangzhuo Xing; Zhixiang Shi; et al. (Frontiers in Physics, 2024)
We report on the effects of 3.5 MeV proton irradiation in RbCa2Fe4As4F2, an iron-based superconductor with unusual properties in between those of the pnictides and of the cuprate high-temperature superconductors. We studied how structural disorder introduced by ion bombardment affects the critical temperature, superfluid density and gap values by combining a coplanar waveguide resonator technique, electric transport measurements and point-contact Andreev-reflection spectroscopy. We find an unusually weak dependence of the superconducting properties on the amount of disorder in this material when compared to other iron-based superconductors under comparable irradiation conditions. The nodal multigap state exhibited by pristine RbCa2Fe4As4F2 is also robust against proton irradiation, with a two-band d-d model being the one that best fits the experimental data.